Numerical Simulation of a Partly Filled Rectangular Tank with Fuel Oil - Farhan Lafta Rashid; Emad Qasem Hussein; Mudhar A. Al-Obaidi; Awesar A. Hussain (Journal of Techniques)
Sloshing refers to a certain kind of fluid movement that changes as it progresses. It possesses properties that are both nonlinear and exceedingly unpredictable, and these properties affect the tank wall. This effect may lead to structural wear, which in turn can cause the tank to fail. Benzene and gasoil liquids are used to test the effect of sloshing liquid and accompanying pressure on the wall tank caused by the baffles in partially full fluid tanks. To attain this, modeling of the interaction between fluid and structure is justified using the finite element analysis while the ANSYS Fluent is used to do the simulation. Specifically, the analysis enables us to anticipate the pressure that is being exerted on the shield, the influence of sloshing on the grounding point forces, and the size of the sloshing waves. The pressure distribution over time indicates a reduction of pressure on the tank wall as a result of utilising a vertical baffle if compared to the case of a tank wall without a baffle. The usage of vertical shields allows for around 20% of the greatest contact energy to be deflected, which is attributed to the potential of generating turbulence and vortices by the baffle.